The effect of H₂O on O₂ reduction in Li-O₂ batteries - Holc, C (2019)
There is significant interest in aprotic lithium-air batteries due to their high theoretical specific energy. During discharge, O2 is reduced at the positive electrode and forms Li2O2. Cells are typically discharged in O2, not air, because CO2 and H2O can interfere with the discharge reaction. However, lithium-air batteries will need to use atmospheric O2 if they are to supplant state-of-the-art lithium-ion cells. Therefore, it is important to establish how detrimental CO2 and H2O are to the battery. The former is well-known to induce the formation of Li2CO3 in Li-O2 batteries, but the recent work has suggested that H2O appears to be beneficial at low concentrations in some solvents (e.g. glyme ethers), increasing discharge capacities and still forming Li2O2, while in other solvents, such as acetonitrile (CH3CN), LiOH is the discharge product. Several mechanisms have been proposed to rationalise these findings, but as yet, there is no consensus on the role of H2O on O2 reduction.